A non-tread formulation for improving tire rolling resistance performance

By using modified white carbon black and modified graphene in the tires to form a heat dissipation mesh structure, and using waste tire raw materials to form recycled rubber powder, the problems of high rolling resistance and high production costs of existing tires are solved, and the effect of reducing fuel consumption and environmental pollution is achieved, while improving the strength and dispersion of the tires are improved.

CN119144059BActive Publication Date: 2025-03-11KUMHO TIRE (TIANJIN) CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604963.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The rolling resistance of existing tires is high, resulting in increased fuel consumption and environmental pollution. The tire industry is facing the problem of tight supply of chemical products and high prices.

Method used

Use waste tire raw materials instead of some rubber raw materials, and improve the tire rolling resistance performance through the synergy between composite filler and recycled rubber powder. The specific method includes surface modification of the white carbon black, using modified graphene and modified white carbon black to form a heat dissipation mesh structure, and forming a recycled rubber powder through atomization and crushing treatment.

Benefits of technology

It effectively reduces the rolling resistance performance of the tire, improves the strength and dispersion of the tire, reduces production costs, and promotes the renewable utilization of used tires.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a non-tread formula for improving the rolling resistance performance of a tire, and relates to the technical field of tire rubber. The present invention uses modified white carbon black and modified graphene as composite fillers of non-tread materials. The presence of the surface branched structure of the two can interact well with rubber, reduce heat generation, and improve rolling resistance. The modified graphene replaces part of the white carbon black to improve the heat dissipation performance. The two interact with each other to maintain the stability of dispersion, solve the problem that the two materials are easy to agglomerate and stack, greatly improve the dispersion of the filler in the rubber, form a heat dissipation network structure inside the tire, and effectively improve the rolling resistance performance of the tire; the present invention uses waste tires to replace part of the rubber raw materials, and through crushing and atomization treatment, it forms recycled rubber powder with an epoxy structure, forms a new internal cross-linking system with the composite filler, improves the tire strength, and improves the rolling resistance performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber, in particular to a non-tread formulation for improving the rolling resistance performance of a tire. Background Art

[0002] Tire rolling resistance is mainly caused by repeated deformation of the tire, which produces hysteresis loss and thus energy loss. Energy is supplied by fuel. Reducing tire rolling resistance means saving fuel. Relevant research shows that tire rolling resistance fuel consumption accounts for about 15% of the vehicle's fuel consumption. Reducing fuel consumption, reducing pollutant exhaust emissions, and promoting ecological sustainable development, the concept of green low rolling resistance tires came into being.

[0003] The current global social and economic development is in a downward trend, and it is facing two serious problems: shortage of fossil resources and environmental pollution. At the same time, the country's emphasis on environmental protection issues is increasing, which has led to tight supply of related chemical products and high prices, making the domestic tire market more competitive and causing profits in the tire industry to decline. Under the premise of ensuring tire performance, reducing production costs has become the most effective way for tire companies to improve economic benefits. Therefore, it is of great significance to develop green, environmentally friendly and renewable materials for tire materials. With the gradual improvement of people's living standards and the rapid development of the logistics industry, the number of private cars and trucks in my country has increased year by year. The increase in the number of vehicles has driven economic development. At the same time, the consumption and wear of automobile tires have also generated a lot of waste tire garbage. The waste tires generated each year increase at a rate of 8% to 10%, resulting in a huge waste of resources. Therefore, the present invention uses waste tire raw materials to replace part of the rubber raw materials to seek the renewable use of waste tires. Summary of the invention

[0004] The object of the present invention is to provide a non-tread formulation for improving the rolling resistance performance of a tire, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a non-tread formulation for improving the rolling resistance performance of a tire, comprising, by weight, 30 to 45 parts of a composite filler, 30 to 45 parts of recycled rubber powder, 50 to 80 parts of natural rubber, 10 to 15 parts of butyl rubber, 0.1 to 1 part of a hindered phenol antioxidant, 3 to 5 parts of zinc oxide, 6 to 8 parts of a plasticizer, 1 to 2 parts of stearic acid, and 1 to 2 parts of sulfur;

[0006] The preparation method of the composite filler is as follows:

[0007] (1) Weigh 2 parts of white carbon black with a mesh size of 1100-1200 pre-activated in vacuum at 110°C for 3 hours, add 5 parts of solvent, heat to 100-120°C, and stir at 200-600 rpm for 0.5-1 hour; then add 0.3-0.5 parts of a mixed treatment agent prepared by hexamethyldisilazane, 0.1-0.2 parts of 3-aminopropyltriethoxysilane and 0.1 parts of deionized water, and then continue to stir at 200-600 rpm for 1-2 hours at 100-120°C. After the reaction is completed, filter, wash the filtrate with ethanol 3 times, and then put the sample into a vacuum drying oven at 90°C for drying;

[0008] (2) Graphene and 3-isocyanatepropyltrimethoxysilane solution are mixed in a ratio of 0.05-5 g:2 mL and placed in a ball mill for ball milling. After the ball milling is completed, modified white carbon black is added, and then a 95 wt% ethanol aqueous solution is added to a solid content of 40%. After vigorous stirring for 1-2 hours at a stirring speed of 400-600 rpm, the mixture is placed in a centrifuge for centrifugation at a speed of 8000-12000 rpm for 20 minutes. After centrifugation, the solid is placed in an oven and dried at 60°C for 48 hours to obtain a composite filler.

[0009] The preparation method of the regenerated rubber powder is as follows: waste tires are placed in an atomization crushing device, and atomization modification treatment is performed while crushing to obtain regenerated rubber powder with a particle size of 5-100 meshes, and then dried at 80° C. for 24 hours.

[0010] Furthermore, the plasticizer is a mixture of one or more of paraffin oil, aromatic oil and paraffin.

[0011] Furthermore, the solvent in step (1) is toluene.

[0012] Furthermore, the vacuum degree in step (1) is -0.085 MPa.

[0013] Furthermore, the ball milling in step (2) is specifically as follows: the rotation speed is 200-400 rad / min, the ball-to-material ratio is 8-15:1, and the ball milling time is 3-7 hours.

[0014] Furthermore, the concentration of 3-isocyanatopropyltrimethoxysilane in the 3-isocyanatopropyltrimethoxysilane solution in step (2) is 0.1-6 vol%, and the solvent is 95 wt% ethanol aqueous solution.

[0015] Furthermore, in step (2), the mass ratio of the modified silica to graphene is 4-10:1.

[0016] Furthermore, the waste tires are waste natural rubber-based tires and waste butyl rubber tires mixed in a ratio of 1:1 by mass.

[0017] Furthermore, the atomization modification uses 10-15 g / L m-chloroperbenzoic acid-cyclohexane solution as the atomization liquid, and the atomization flow rate is 200-350 L / h.

[0018] Furthermore, the butyl rubber is butyl rubber 065.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] (1) The present invention uses hexamethyldisilazane as the main component and 3-aminopropyltriethoxysilane as the auxiliary component to perform composite surface modification on silica. The branched chain structure on the particle surface enhances the dispersibility of the particles. The particles are added into rubber as fillers for comprehensive modification, interact well with the rubber, reduce heat generation, and improve rolling resistance. Then, graphene modified with 3-isocyanatepropyltrimethoxysilane replaces part of the silica to improve heat dissipation performance. The modified graphene and modified silica surface groups interact with each other to maintain dispersion stability, solving the problem that the two materials are easy to agglomerate and stack, greatly improving the dispersibility of the filler in the rubber, and forming a heat dissipation network structure inside the tire, effectively improving the rolling resistance of the tire. The present invention utilizes the synergistic effect between mixed fillers to give full play to the advantages of each filler;

[0021] (2) The present invention utilizes waste tires to replace part of the rubber raw materials. Through crushing and atomization treatment, the waste tires are formed into rubber powder. At the same time, an epoxidant is used for atomization to convert the unsaturated bonds in the waste tire rubber into epoxy groups to form recycled rubber powder. A new internal cross-linking system is formed with the composite filler, thereby increasing the tire strength and improving the rolling resistance. In addition, during the vulcanization process, the filler of the silane molecule section and the rubber polymer produce more particle-polymer structures, thereby increasing the strength of the tire material. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Example 1: A non-tread formulation for improving the rolling resistance performance of a tire, comprising, by weight, 30 parts of a composite filler, 30 parts of recycled rubber powder, 50 parts of natural rubber, 10 parts of butyl rubber 065, 0.1 parts of a hindered phenol antioxidant, 3 parts of zinc oxide, 6 parts of paraffin oil, 1 part of stearic acid, and 1 part of sulfur;

[0024] The preparation method of the composite filler is as follows:

[0025] (1) Weigh 2 parts of 1100 mesh white carbon black pre-activated at 110°C and a vacuum degree of -0.085 MPa for 3 hours, add 5 parts of toluene, heat to 110°C, and stir at 600 rpm for 0.5 hours; then add 0.5 parts of a mixed treatment agent prepared by hexamethyldisilazane, 0.1 parts of 3-aminopropyltriethoxysilane and 0.1 parts of deionized water, and continue to stir at 400 rpm for 1.5 hours at 100°C. After the reaction is completed, filter, wash the filtrate with ethanol 3 times, and then put the sample into a vacuum drying oven at 90°C and dry it at a vacuum degree of -0.085 MPa for 10 hours;

[0026] (2) Graphene and 3-isocyanatepropyltrimethoxysilane solution were mixed in a ratio of 1g:2mL and placed in a ball mill for ball milling. After the ball milling was completed, modified silica was added, and the mass ratio of modified silica to graphene was 8:1. Then, 95wt% ethanol aqueous solution was added until the solid content was 40%. After 1.5 hours of vigorous stirring at a stirring speed of 600rpm, the mixture was placed in a centrifuge for centrifugation at a speed of 12000rpm for 20min. After centrifugation, the solid was placed in an oven and dried at 60°C for 48h to obtain a composite filler. The ball milling process was specifically as follows: a rotation speed of 400rad / min, a ball-to-material ratio of 8:1, and a ball milling time of 7h. The concentration of 3-isocyanatepropyltrimethoxysilane in the 3-isocyanatepropyltrimethoxysilane solution was 5vol%, and the solvent was 95wt% ethanol aqueous solution.

[0027] The preparation method of the reclaimed rubber powder is as follows: waste tires are placed in an atomization crushing device, the mass ratio of waste natural rubber-based tires to waste butyl rubber tires in the waste tires is 1:1, and atomization modification treatment is performed while crushing, and a 14g / L m-chloroperbenzoic acid-cyclohexane solution is used as an atomization liquid for atomization modification, and the atomization flow rate is 350L / h to obtain a reclaimed rubber powder with a particle size of 60 mesh, and then dried at 80°C for 24h.

[0028] Example 2; The difference between Example 2 and Example 1 is: 45 parts of composite filler, 45 parts of recycled rubber powder, 80 parts of natural rubber, 15 parts of butyl rubber 065, 1 part of hindered phenol antioxidant, 5 parts of zinc oxide, 8 parts of paraffin oil, 2 parts of stearic acid, 2 parts of sulfur, and the remaining steps are the same as Example 1.

[0029] Example 3; The difference between Example 3 and Example 1 is: 40 parts of composite filler, 38 parts of recycled rubber powder, 70 parts of natural rubber, 12 parts of butyl rubber 065, 0.2 parts of hindered phenol antioxidant, 4 parts of zinc oxide, 7 parts of paraffin oil, 1 part of stearic acid, 1 part of sulfur, and the remaining steps are the same as Example 1.

[0030] Example 4; The difference between Example 4 and Example 1 is: 33 parts of composite filler, 34 parts of recycled rubber powder, 80 parts of natural rubber, 10 parts of butyl rubber 065, 0.1 parts of hindered phenol antioxidant, 4 parts of zinc oxide, 6 parts of paraffin oil, 2 parts of stearic acid, 2 parts of sulfur, and the remaining steps are the same as Example 1.

[0031] Example 5; The difference between Example 5 and Example 1 is: 42 parts of composite filler, 41 parts of recycled rubber powder, 75 parts of natural rubber, 13 parts of butyl rubber 065, 0.7 parts of hindered phenol antioxidant, 4 parts of zinc oxide, 6 parts of paraffin oil, 1 part of stearic acid, 1 part of sulfur, and the remaining steps are the same as Example 1.

[0032] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that hexamethyldisilazane is not added, and the relevant steps are changed to: weigh 2 parts of 1100 mesh white carbon black pre-activated at 110°C and a vacuum degree of -0.085MPa for 3h, add 5 parts of toluene and heat to 110°C, and stir at 600rpm for 0.5h; then add 0.1 parts of a mixed treatment agent prepared by 3-aminopropyltriethoxysilane and 0.1 parts of deionized water, and then continue to stir at 400rpm for 1.5h at 100°C. After the reaction is completed, filter, wash the filtrate with ethanol 3 times, and then put the sample into a vacuum drying oven at 90°C and dry it at a vacuum degree of -0.085MPa for 10h; the remaining steps are the same as Example 1.

[0033] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that 3-aminopropyltriethoxysilane is not added, and the relevant steps are changed to: weigh 2 parts of 1100 mesh white carbon black pre-activated at 110°C and a vacuum degree of -0.085MPa for 3h, add 5 parts of toluene and heat to 110°C, and stir at 600rpm for 0.5h; then add 0.5 parts of a mixed treatment agent prepared by hexamethyldisilazane and 0.1 parts of deionized water, and then continue to stir at 400rpm for 1.5h at 100°C. After the reaction is completed, filter, wash the filtrate with ethanol 3 times, and then put the sample into a vacuum drying oven at 90°C and dry it at a vacuum degree of -0.085MPa for 10h; the remaining steps are the same as Example 1.

[0034] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that 3-isocyanatepropyltrimethoxysilane is not used to modify graphene, and the relevant steps are changed to: graphene and modified white carbon black are mixed at a mass ratio of 1:8, and then 95wt% ethanol aqueous solution is added to a solid content of 40%. After 1.5 hours of vigorous stirring at a stirring speed of 600rpm, the mixture is placed in a centrifuge for centrifugation at a speed of 12000rpm for 20min. After centrifugation, the solid is placed in an oven and dried at 60°C for 48h to obtain a composite filler. The remaining steps are the same as in Example 1.

[0035] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the atomization-modified waste rubber powder is not used, and the relevant steps are changed to: putting the waste tires into the crushing equipment, the mass ratio of the waste natural rubber-based tires and the waste butyl rubber tires in the waste tires is 1:1, and the rubber powder with a particle size of 60 mesh is obtained, and the remaining steps are the same as Example 1.

[0036] Effect example

[0037] The non-tread formulations prepared in the examples and comparative examples were mixed in proportion, discharged at 148°C, left for 4 hours, pressed into sheets, and then vulcanized at 160°C for 15 minutes. The properties of the formulated rubber materials and samples were measured, and the results are shown in Table 1. Table 1 shows the performance analysis results of the rubber materials and tire samples using Examples 1 to 5 of the present invention and Comparative Examples 1 to 4.

[0038] Table 1

[0039] Tensile strength (MPa) Elongation at break (%) Tear strength (kN / m) Rebound (%) Rolling resistance coefficient Example 1 20.2 408 37 40 94 Example 2 20.8 423 41 42 88 Example 3 20.6 417 41 41 92 Example 4 20.4 412 39 40 93 Example 5 20.7 420 40 40 90 Comparative Example 1 19.9 400 34 37 102 Comparative Example 2 20.1 402 35 39 100 Comparative Example 3 18.5 390 30.5 38 105 Comparative Example 4 19.0 388 32 36 101

[0040] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention uses hexamethyldisilazane and 3-aminopropyltriethoxysilane to modify the white carbon black, strengthen the surface branched chain structure, enhance the dispersibility of the particles, and the presence of the surface branched chain structure can interact well with the rubber, reduce heat generation, and improve rolling resistance performance; and then replace part of the white carbon black with graphene modified with 3-isocyanatopropyltrimethoxysilane to improve the heat dissipation performance, and the modified graphene and the modified white carbon black surface groups interact with each other to maintain the stability of the dispersion, thereby solving the problem that the two materials are easy to agglomerate and stack. , greatly improving the dispersion of fillers in rubber, forming a heat dissipation network structure inside the tire, and effectively improving the rolling resistance of the tire; the present invention uses waste tires to replace part of the rubber raw materials, and through crushing and atomization treatment, it forms rubber powder. At the same time, an epoxidant is used for atomization to convert the unsaturated bonds in the waste tire rubber into epoxy groups to form recycled rubber powder, which forms a new internal cross-linking system with the composite filler, thereby improving the strength of the tire and improving the rolling resistance. In addition, during the vulcanization process, the filler of the silane molecule and the rubber polymer produce more particle-polymer structures, thereby improving the strength of the tire material.

[0041] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all changes within the meaning and range of equivalent elements of the claims be included in the invention. Any sign in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A non-tread formulation for improving the rolling resistance performance of a tire, comprising, by weight, 30-45 parts of a composite filler, 30-45 parts of recycled rubber powder, 50-80 parts of natural rubber, 10-15 parts of butyl rubber, 0.1-1 parts of a hindered phenol antioxidant, 3-5 parts of zinc oxide, 6-8 parts of a plasticizer, 1-2 parts of stearic acid, and 1-2 parts of sulfur, characterized in that: The preparation method of the composite filler is as follows: (1) Weigh 2 parts of white carbon black with a mesh size of 1100-1200 pre-activated in vacuum at 110°C for 3 hours, add 5 parts of solvent, heat to 100-120°C, and stir at 200-600 rpm for 0.5-1 hour; then add 0.3-0.5 parts of a mixed treatment agent prepared by hexamethyldisilazane, 0.1-0.2 parts of 3-aminopropyltriethoxysilane and 0.1 parts of deionized water, and then continue to stir at 200-600 rpm for 1-2 hours at 100-120°C. After the reaction is completed, filter, wash the filtrate with ethanol 3 times, and then put the sample into a vacuum drying oven at 90°C for drying; (2) Graphene and 3-isocyanatepropyltrimethoxysilane solution are mixed in a ratio of 0.05-5 g:2 mL and placed in a ball mill for ball milling. After the ball milling is completed, modified white carbon black is added, and then a 95 wt% ethanol aqueous solution is added to a solid content of 40%. After vigorous stirring for 1-2 hours at a stirring speed of 400-600 rpm, the mixture is placed in a centrifuge for centrifugation at a speed of 8000-12000 rpm for 20 minutes. After centrifugation, the solid is placed in an oven and dried at 60°C for 48 hours to obtain a composite filler. The preparation method of the recycled rubber powder is as follows: waste tires are placed in an atomizing crushing device, and atomizing modification treatment is performed while crushing, and a 10-15 g / L m-chloroperbenzoic acid-cyclohexane solution is used as an atomizing liquid for atomizing modification, and the atomizing flow rate is 200-350 L / h to obtain a recycled rubber powder with a particle size of 5-100 mesh, and then dried at 80° C. for 24 hours.

2. A non-tread formulation for improving tire rolling resistance performance according to claim 1, characterized in that: The plasticizer is a mixture of one or more of paraffin oil, aromatic oil and paraffin.

3. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The solvent in step (1) is toluene.

4. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The vacuum degree in step (1) is -0.085 MPa.

5. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The ball milling in step (2) is specifically as follows: the rotation speed is 200-400 rad / min, the ball-to-material ratio is 8-15:1, and the ball milling time is 3-7 hours.

6. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The concentration of 3-isocyanatopropyltrimethoxysilane in the 3-isocyanatopropyltrimethoxysilane solution in step (2) is 0.1-6 vol%, and the solvent is 95 wt% ethanol aqueous solution.

7. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The mass ratio of the modified silica to graphene in step (2) is 4-10:

1.

8. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The waste tires are waste natural rubber-based tires and waste butyl rubber tires mixed in a ratio of 1:1 by mass.

9. The non-tread formulation for improving the rolling resistance performance of a tire according to claim 1, characterized in that: The butyl rubber is butyl rubber 065.

Citation Information

Patent Citations

  • Non-pneumatic tire rubber material with modified white carbon black filler

    CN114276597A

  • Filler composition capable of reducing rolling resistance of tire, low-rolling-resistance tire rubber material, preparation method of low-rolling-resistance tire rubber material and tire

    CN118909326A